2013
DOI: 10.1002/cbf.2984
|View full text |Cite
|
Sign up to set email alerts
|

Moderate physical exercise attenuates the alterations of feeding behaviour induced by social stress in female rats

Abstract: Epidemiological studies have demonstrated that stress-related disorders, such as the increase on the caloric intake, are twice as common in women as in men, but surprisingly, very few studies have been tested this subject on female experimental animals. Additionally, it has been proposed that regular physical exercise can improve the deleterious effects of stress. Therefore, the present longitudinal study, performed in female rats, aimed to test the influence of chronic stress (ST) imposed by social isolation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 62 publications
2
17
0
2
Order By: Relevance
“…In our previous study, we demonstrated that isolated females rats increase their intake of fat and that was associated to increase in corticosterone [3], such as in others studies [7,8,16]. In this study, therefore, we test the hypothesis that the increase in corticosterone may be due the increase in high fat food intake per se and not only due the methodology used to induce social stress and verify if high fat food and stress affect mitochondrial homeostasis.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…In our previous study, we demonstrated that isolated females rats increase their intake of fat and that was associated to increase in corticosterone [3], such as in others studies [7,8,16]. In this study, therefore, we test the hypothesis that the increase in corticosterone may be due the increase in high fat food intake per se and not only due the methodology used to induce social stress and verify if high fat food and stress affect mitochondrial homeostasis.…”
Section: Introductionmentioning
confidence: 65%
“…The fecal samples were collected three times: at beginning of experiment, after two and six weeks. The collection and the treatment was performed as described previously [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…O exercício físico tem sido testado para aliviar diversos tipos de estresse experimentalmente induzidos, como isolamento social [5,30], ruídos [35], imobilização, frio [31], privação de alimentos e água [14], dentre outros. Há indícios de que o tipo e a intensidade do exercício, bem como o modelo animal utilizado, podem influenciar nas respostas hormonais e comportamentais [36].…”
Section: Artigo Originalunclassified
“…Em estudo com ratos, o exercício físico de baixa intensidade mostrou-se como um atenuador de alterações tanto de insulina e metabólitos da corticosterona, quanto do comportamento alimentar promovido pelo estresse social induzido pelo isolamento, com provável ação sobre o eixo hipotalâmico-pituitário-adrenal [5]. Observou-se que o exercício retarda o desenvolvimento de neurite autoimune em ratos [6].…”
Section: Introductionunclassified